A Type-III Insect Geranylgeranyl Diphosphate Synthase with a Novel Catalytic Property - Zhang, Hao; Li, Zheng-Xi (Protein and Peptide Letters, 2014)
Geranylgeranyl diphosphate synthase (GGPP synthase or GGPPS) is among the short-chain prenyltransferases, catalyzing the formation of the acyclic precursor GGPP for the biosynthesis of a variety of isoprenoids. GGPPSs have been extensively studied in plants, eubacteria, archaebacteria, yeast and mammals, but up to now information about an insect GGPPS is still scarce. Here we cloned the cDNA encoding an insect GGPPS from the cotton aphid (designated as AgGGPPS). AgGGPPS had an open reading frame of 930 bp, coding for 309 amino acids, with a theoretical pI/Mw of 6.21/35.7kDa. Sequence analysis showed that the amino acid sequence of AgGGPPS included the conserved aspartaterich motifs characterized by all prenyltransferases known to date, and could be classified as type-III GGPPS. Phylogenetic analysis showed that all animal GGPPSs were placed in a large group next to fungal GGPPS, and plant and bacterial GGPPSs formed another large group. AgGGPPS was over-expressed in Escherichia coli, and recombinant protein was purified by affinity chromatography. In vitro enzymatic activity assay coupled with product identification by gas chromatography- mass spectrometry demonstrated that AgGGPPS could catalyzed the formation of GGPP with DMAPP, GPP or FPP as the allylic cosubstrates in the presence of IPP, suggesting that AgGGPPS accepted not only FPP but also GPP and DMAPP as the allylic cosubstrate, different from other type-III GGPPSs which accepted only FPP as the allylic cosubstrate. This is the first report that a novel catalytic property exists in the type-III animal GGPPSs.
Keywords: Functional expression